Pathways Through Public Services for Maltreated Children in Care: A Scoping Review of Studies Using Linked Administrative Data - Cowley, Laura; Bandyopadhyay, Amrita; Kennedy, Natasha; Fallesen, Peter; Quantin, Catherine; Brooks, Daisy; Bektas, Can; Brophy, Sinead (International Journal of Population Data Science, 2026)
Background Understanding how children in care interact with public services is essential to improving outcomes. This review aims to map studies that used linked administrative data to examine service pathways and outcomes for maltreated children in care, and forms part of the EU-funded SERENA project - Assessing and improving access to health and social care SErvices for children RENdered vulnerable by Abuse. Methods We searched eight databases, identifying 1086 potentially relevant records. Of these, 396 were selected for review and screened in duplicate. We included 137 studies across the globe that examined contact with services, including health, social care, education, justice, homelessness, and employment before or after children went into care. Results will be tabulated and narratively synthesized. Findings Preliminary findings from the education sector suggest that, compared to their peers, care-experienced children exhibit poorer educational attainment, higher levels of absence, are more likely to drop out of or be excluded from school, and are less likely to enroll in higher education. Placement instability and placement with non-kin foster carers emerged as risk factors for poor educational outcomes. There were few differences in educational attainment between children in care and maltreated children who were not in care. Conclusions This review will clarify how linked administrative data has been used to understand service pathways of maltreated children in care. Insights from the review will inform recommendations for policy and practice as well as future research in the SERENA project, specifically planned linked routine data work in Wales, England, and Denmark.